Inclusion Strategies on @greenpeaceid Instagram Posts: A Critical Discourse Analysis - Wahyuni, Ian; Nurkhasanah, Binti; Nurmila, Nurmila (Universitas Airlangga, 2023)
The study aims to analyze the inclusion strategies in the discourse regarding environmental issues uploaded by @greenpeaceid Instagram account. This research was conducted based on a descriptive qualitative approach. The data collection and analysis were carried out using read and record techniques by virtually observing the Instagram account of @greenpeaceid. Furthermore, the data were categorized and analyzed according to van Leeuwen's critical discourse analysis, namely social actor representation theory. The data were collected from 24 October 2022 to 9 November 2022. The research data were in forms of words, phrases, and sentences contained in the captions used by @greenpeaceid. The results show that in representing the social actors involved in the discourse regarding environmental issues, the @greenpeaceid used the strategy of differentiation, objectivation, indetermination, nominations, and association. The presence of actors/events in discourse is considered to be able to clearly describe the involvement of related social actors in their campaigns to overcome the climate crisis. Therefore, the intended goals and information can be conveyed to the readers. Furthermore, the analysis shows that the @greenpeaceid account shows the ideological stance of pro-government which they consider as partners in efforts to overcome the climate crisis.